2015
DOI: 10.4103/0019-509x.175599
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of primary non-metastatic breast cancer: A single institution experience

Abstract: Over 90% of non-metastatic breast cancer patients present with stagesII and III disease and a significant proportion develop distant metastasis accounting for overall long-term outcome inferior to developed countries. Efforts should be directed to raise the level of health awareness and screening programs to improve early detection in Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Factors affecting DFS and OS: age, lymph node involvement, lymphovascular invasion, tumour stage, adjuvant anthracycline-based chemotherapy and type of surgery (not significant for DFS). Three-year DFS and OS:72.0 and 93.0%, respectively Jamshed et al 2015, India (Asia) [ 13 ] Clinical outcome of primary NMBC: A single institution experience Fifteen-year single-center retrospective study:2829 cases The median follow-up: 4.4 years. Recurrence following primary treatment was seen in 35% of the patients: 5% local, 1% regional, and 29% distant.…”
Section: Resultsmentioning
confidence: 99%
“…Factors affecting DFS and OS: age, lymph node involvement, lymphovascular invasion, tumour stage, adjuvant anthracycline-based chemotherapy and type of surgery (not significant for DFS). Three-year DFS and OS:72.0 and 93.0%, respectively Jamshed et al 2015, India (Asia) [ 13 ] Clinical outcome of primary NMBC: A single institution experience Fifteen-year single-center retrospective study:2829 cases The median follow-up: 4.4 years. Recurrence following primary treatment was seen in 35% of the patients: 5% local, 1% regional, and 29% distant.…”
Section: Resultsmentioning
confidence: 99%
“…For example, CK2 inhibitors decrease cell migration and invasion in human adenocarcinoma and NSCLC cell lines, seemingly through downregulation of MMP-2 transcript expression and activity via the ERK pathway [ 54 ]. In SCLC and LCLC (large cell lung cancer), cell proliferation, but not cell invasion, is highly sensitive to Quinalizarin [ 55 ]. In contrast, in one adenocarcinoma cell line, invasion and apoptosis, but not proliferation, were sensitive to Quinalizarin [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In SCLC and LCLC (large cell lung cancer), cell proliferation, but not cell invasion, is highly sensitive to Quinalizarin [ 55 ]. In contrast, in one adenocarcinoma cell line, invasion and apoptosis, but not proliferation, were sensitive to Quinalizarin [ 55 ]. In other adenocarcinoma cell lines, Quinalizarin only leads to increased apoptosis [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, prognosis in the first 3 years of ER(+) tumors was shown to be good, although survival in the longer term was fairly poor. Gradually, endocrine therapy resistance is the main factor that blocks the success of hormonal treatment [14]. Chemotherapy in HR-negative patients is known to improve DFS and OS [7].…”
Section: Clinical Features and Differences Of Tumor Subgroupsmentioning
confidence: 99%
“…Additionally, 25-50% of ER+PR+ tumors are resistant to hormonal treatment. Genetic and non-genetic interferences between the ER and growth factors may lead to hormone resistance [14], but the exact mechanism that is implicated has not yet been understood. Genetic testing is not commonly performed to determine tumor subtypes or select treatment, and treatment alternatives are usually applied based on the receptor and clinicopathological data.…”
Section: Prognosis Survival and Risk Factors That Affect Themmentioning
confidence: 99%